Effect of BMI on Prolonged Abstinence after Smoking Cessation Treatment: A Retrospective Cohort Study - Frallonardo, Fernanda P.; Lima, Danielle Ruiz; Carvalho, Carlos F. C.; Loreto, Aline Rodrigues; Guimarães-Pereira, Bruna Beatriz Sales; Ismael, Flavia; Torales, Julio; Ventriglio, Antonio; de Andrade, Arthur Guerra; da Silva Bizário, João Carlos; Castaldelli-Maia, João Mauricio (Current Drug Research Reviews, 2021)
Background: Despite the well-documented relationship between weight gain and poorer cessation outcomes among smokers, the role of the former (baseline) weight in smoking cessation is insufficiently investigated. We hypothesized that patients with higher baseline body mass index( BMI) have a worse prognosis in tobacco cessation. Objectives: This retrospective clinical cohort study aimed to investigate the role of the baseline BMI on abstinence over 12 months after participation in smoking cessation treatment conducted in a middle-income country (n = 664). Methods: Data from a 6-week smoking cessation protocol performed in a Psychosocial Care Unit (CAPS) were used. The protocol included four medical consultations and six Cognitive-Behavioral Therapy (CBT) group sessions. Initially, 1,213 participants were evaluated for the study, but only the participants whose telephone contact was successful were included in the outcome analyses. The attrition rate was 45.3%. Continuous and categorical (normal, overweight, and obesity) BMI values were computed. Survival regression models were used to test the associations between BMI and the 12-month abstinence outcome. Self-report 4-week abstinence at the end of treatment was also investigated using logistic regression models. Results: Baseline BMI had no significant effect on both short (4-week-point abstinence) and long (12-month prolonged abstinence) treatment outcomes. Conclusion: The possible influence of the baseline BMI on smoking cessation outcomes, especially considering prolonged abstinence, was not corroborated by our results. Regardless of our results, the detrimental health outcomes due to the combination of obesity/overweight and smoking justify that these subgroups of individuals be continuously targeted for adequate smoking prevention and treatment.
Keywords: body mass index